2017
DOI: 10.7547/15-125
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Fasciitis—A Comparison of Treatment with Intralesional Steroids versus Platelet-Rich Plasma

Abstract: We can conclude that the use of PRP is an effective treatment method for patients with plantar fasciitis who do not respond to conservative treatment because PRP demonstrates an efficacy equal to that of steroids. However, the cost and the time for preparation the PRP are two of the disadvantages of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 31 publications
5
80
2
Order By: Relevance
“…Moreover, they concluded that the use of PRP is an effective treatment method for patients with plantar fasciitis who do not respond to conservative treatment because PRP demonstrates an efficacy equal to that of steroids. 32 In contrast to our results, a meta-analysis conducted by Yang et al 2007 concluded that PRP is superior to steroid treatments for long-term pain relief; however, significant differences were not observed between short and intermediate effects. 35 In our series, no difference was seen in pain or functional result in between the two groups at any of the follow-up visits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, they concluded that the use of PRP is an effective treatment method for patients with plantar fasciitis who do not respond to conservative treatment because PRP demonstrates an efficacy equal to that of steroids. 32 In contrast to our results, a meta-analysis conducted by Yang et al 2007 concluded that PRP is superior to steroid treatments for long-term pain relief; however, significant differences were not observed between short and intermediate effects. 35 In our series, no difference was seen in pain or functional result in between the two groups at any of the follow-up visits.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean age was similar to another study done by Acosta-Olivo et al in 2017 who reported the average age of the patients was 44.8 years (range, 24-61 years). 32 Also another study of PRP injection done by Ragab et al in 2012, on 25 patients with chronic plantar fasciitis, reported mean age of 44 years in their patients. 33 In our study a total of 120 sites were affected and left side was more common.…”
Section: Discussionmentioning
confidence: 94%
“…22,[25][26][27] Females were more frequently affected (52% in PRP group and 57% in the corticosteroid group) in our study. Though gender differences have not been shown in patients with planter fasciitis, a recent study observed a slight male preponderance (57.5%) contrary to our finding.…”
Section: Discussionsupporting
confidence: 45%
“…22 Others also have reported equal efficacy for both PRP and corticosteroid therapy. 25,26 Functional assessment in terms of the AOFAS score also showed that corticosteroid is more effective for short term relief and PRP is more effective for long term relief as evidenced by a significant increase in AOFAS in the Corticosteroid group compared to PRP group at 6 weeks (p<0.001) which increased in the PRP group at 3 months (85.72) and still further increased at 6 months (90.03). However it decreased in the corticosteroid group at 3 months (78.57) and 6 months (74.67).…”
Section: Discussionmentioning
confidence: 92%
“…PRP injections have been investigated in hip and knee osteoarthritis, ankle sprains, healing of non-united fractures, tennis elbow, chronic refractory patellar tendi-nopathy, plantar fasciitis and sports injuries in many clinical studies (17)(18)(19) . A prospective randomized controlled study concluded that local application of autologous PRP improved tendon healing in patients undergoing arthroscopic rotator cuff repair and reduced pain in the first postoperative months (20) .…”
Section: Orthopedicsmentioning
confidence: 99%